2015
DOI: 10.1038/ncomms9561
|View full text |Cite
|
Sign up to set email alerts
|

High catalytic activity of oriented 2.0.0 copper(I) oxide grown on graphene film

Abstract: Metal oxide nanoparticles supported on graphene exhibit high catalytic activity for oxidation, reduction and coupling reactions. Here we show that pyrolysis at 900 °C under inert atmosphere of copper(II) nitrate embedded in chitosan films affords 1.1.1 facet-oriented copper nanoplatelets supported on few-layered graphene. Oriented (1.1.1) copper nanoplatelets on graphene undergo spontaneous oxidation to render oriented (2.0.0) copper(I) oxide nanoplatelets on few-layered graphene. These films containing orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 58 publications
6
68
0
Order By: Relevance
“…In a related precedent, it has reported that Cu2O nanocrystals supported on G exhibit a much enhanced catalytic activity. [19] It is known that pyrolysis converts chitosan and other filmogenic natural polysaccharides into G. [20] Apparently, the fibrils of chitosan, the carbonaceous residues derived from them and the evolving N-doped G arrest in each step the growth of Au NPs being also formed simultaneously in the process as consequence of the reductive conditions of the G synthesis and the lack of solubility of Au on carbon. [21,22] While many metals form metal carbides upon heating the metal with carbon at high temperatures, the noble character of Au results in a phase segregation leading to the synchronous formation of N-doped G and Au NPs.…”
mentioning
confidence: 99%
“…In a related precedent, it has reported that Cu2O nanocrystals supported on G exhibit a much enhanced catalytic activity. [19] It is known that pyrolysis converts chitosan and other filmogenic natural polysaccharides into G. [20] Apparently, the fibrils of chitosan, the carbonaceous residues derived from them and the evolving N-doped G arrest in each step the growth of Au NPs being also formed simultaneously in the process as consequence of the reductive conditions of the G synthesis and the lack of solubility of Au on carbon. [21,22] While many metals form metal carbides upon heating the metal with carbon at high temperatures, the noble character of Au results in a phase segregation leading to the synchronous formation of N-doped G and Au NPs.…”
mentioning
confidence: 99%
“…It is suggested that, as claimed previously, chitosan and the carbonaceous residues derived therefrom during the different phases of the pyrolysis are thwarting and restricting the growth of the Fe/Co NPs by interacting with them . In related precedents, it has been found that Au, Cu, and even TiO 2 and CeO 2 NPs of relatively small size are formed if the procedure starts with the corresponding metal ions embedded in chitosan.…”
Section: Resultsmentioning
confidence: 99%
“…In line with this orientation issue, a major breakthrough was recently reported by Garcia et al., where the virtues of chitosan were put in practice not only for graphitization but also to direct metal growth anisotropically (Figure ). Instead of the conventional two‐step strategy that consists of i) graphitization of the polysaccharide followed by ii) metal impregnation, a one‐pot pyrolysis of Cu chitosan brings new perspectives to the selective synthesis of preferential faceted metals or metal oxide particulates on heterogeneous support, where oriented (2 0 0) Cu 2 O grown on graphene films were successfully isolated …”
Section: Figurementioning
confidence: 99%
“…Reduction treatment by hydrogen restores the original (1 1 1) Cu 0 from the former phase. In turn, the presence of Cu in the chitosan film affects the chemical composition of the resulting graphene by completely removing doping with N atoms, which is in sharp contrast to Cu‐free chitosan films that afford N‐doped graphene …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation